Pathophysiology and Perioperative Management of Sickle Cell Disease. Issue 6 (June 2015) - Paradowski, K
Sickle cell disease has become the most common genetic condition in some European countries (Roberts & De Montalembert 2007). The disease is characterised by the painful sickle cell crisis often experienced by sufferers. This article sets out to examine the pathophysiology of this disease, alongside the factors that perioperative practitioners need to be aware of in order to reduce the risk of triggering a sickle cell crisis.